Environmental Surveillance of Landfills for Solid Waste and a Workable Approach Adopting to Make a Brick from Landfill Waste (International Journal of Innovative Research in Engineering & Management, 2022)
Rapid urbanisation and industrialization  have resulted in two major consequences. The waste of  resources and the accumulation of rubbish are two such  examples. As people's living standards rise, they produce  vast quantities of municipal solid waste. This waste is then  either sent to landfills or burned openly, polluting the air  across the city. For this reason, it is essential to develop and  execute a reliable solid waste management system that  would help lessen the environmental damage caused by  municipal landfills. With this in mind, the current  investigation was conducted to learn more about the issues  surrounding MSW dump sites close to the Banvhare Dada  Nuwakot disposal facility in Nepal. The purpose of this  research is to monitor and analyse land-based municipal  solid waste problems and to evaluate the practicability of  municipal solid waste energy recovery. At the dump site,  the atmosphere and air quality were monitored, as well as  soil and water tests. The quantity of leachate elements in  the subsoil is also being determined as part of this  investigation to help in future site appraisal. Results from a  physical and chemical analysis of municipal solid waste  (MSW) collected from the landfill showed that the  landfill's trash had a biodegradable fraction of 79 percent,  a higher proportion of moisture levels, and a volatile solid  content of 76 percent. Thus, bio-methanation of municipal  solid waste may proceed. Cost effectiveness, resource  conservation, reduced greenhouse gas emissions, and other  benefits are all features of plastic soil brick. The "Eco Bricks" or plastic soil bricks, also known as, are formed of  plastic waste and may be utilised for construction but are  otherwise hazardous to all living things. Compared to  bricks made of fly ash, it improves compressive strength. Alkalis' water-absorbing capacity was significantly  decreased by the usage of plastic soil blocks. Further study  would enhance the quality and durability of plastic soil  bricks because of their multiple benefits.
Keywords: Physical composition of MSW; Chemical composition of MSW; Leachate Charaterization; Soil Characteristics; Brick Result